Human infectiousness and parasite load in chronic patients seropositive for Trypanosoma cruzi in a rural area of the Argentine Chaco - Macchiaverna, Natalia Paula (2019)
A key parameter in the transmission of vector-borne infections, including Chagas disease, is the ability of the different host species to transmit the parasite to the vector (infectiousness). Here, we determined infectiousness to the vector of Trypanosoma cruzi-seropositive humans examined by artificial xenodiagnosis (XD), established its relationship with T. cruzi DNA levels (a surrogate of intensity of parasitemia) quantified by real-time PCR (qPCR), and assessed whether infectiousness was associated with the body mass index (BMI), age, ethnic background and parasite genotype. XD was performed to 117 T. cruzi-seropositive residents from Pampa del Indio and parasite load was quantified in 81 of them. Using optical microscopy (OM) 33.6% of the seropositive people tested were infectious and this fraction nearly doubled (66.0%) when XD triatomines were examined by kDNA-PCR. The mean infectiousness (defined as the percentage of all infected triatomines detected by OM at any time point among the total number of insects examined by OM 30 days post-feeding) was 5.2%, and the mean parasite load was 0.51 parasite equivalents per ml. Infectiousness to the vector was associated negatively with age and BMI, and positively with the detection of parasitemia by kDNA-PCR, and parasite load by qPCR in bivariate analysis. Patients with a positive XD by OM exhibited a significantly higher mean parasite load. Using multiple regression, infectiousness was associated with parasite load (positively) and with the household presence of T. infestans and Qom ethnic group (negatively); no significant association was observed with age or its interaction with ethnicity. We did not find significant associations between identified DTUs and infectiousness or parasite load. Infectiousness was aggregated: 18% of the people examined by XD generated 80% of the infected triatomines. Detecting and treating the super-infectious fraction of the infected human would disproportionally impact on domestic transmission risks. Nonetheless, treatment of all eligible infected people who meet the inclusion criteria regardless of their parasitemia should be ensured to improve their prognosis.